2020
DOI: 10.2196/preprints.19435
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitigating COVID-19 impact on the Portuguese population mental health: the opportunity that lies in Digital Mental Health (Preprint)

Abstract: UNSTRUCTURED COVID-19 mitigation measures present unprecedent challenges in mental healthcare delivery, posing high risk to the mental health of populations. Ensuring safe and equitable access to mental healthcare requires resorting to innovative psychosocial intervention strategies such as, Digital Mental Health. In this perspective piece, we discuss how timely implementation of a comprehensive Digital Mental Health strategy, coupling research, education, implementation and quality ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…Generally, patients rated therapeutic alliance and empathy higher than psychotherapists, which is consistent with previous results (Lopez et al, 2019;Simpson & Reid, 2014). This might be influenced by psychotherapists' scepticism towards digital psychotherapy (Feijt et al, 2018;Mendes-Santos et al, 2020).…”
Section: Therapeutic Alliance and Empathysupporting
confidence: 90%
See 3 more Smart Citations
“…Generally, patients rated therapeutic alliance and empathy higher than psychotherapists, which is consistent with previous results (Lopez et al, 2019;Simpson & Reid, 2014). This might be influenced by psychotherapists' scepticism towards digital psychotherapy (Feijt et al, 2018;Mendes-Santos et al, 2020).…”
Section: Therapeutic Alliance and Empathysupporting
confidence: 90%
“…VCT is an effective treatment for psychiatric disorders, as a substantial body of evidence shows (Berryhill et al, 2019;Bouchard et al, 2020;Fernandez et al, 2021;Liu et al, 2020;Norwood et al, 2018;Stubbings et al, 2013;Tuerk et al, 2018). Nevertheless, negative attitudes towards VCT exist due to different concerns, for example, about the therapeutic alliance (Feijt et al, 2018;Knott et al, 2020;Lal & Adair, 2014;Lopez et al, 2019;Mendes-Santos et al, 2020). In this respect, our study demonstrated that patients experienced a comparable therapeutic alliance with their psychotherapists independently from F2F or VCT.…”
Section: Limitations and Future Directionsmentioning
confidence: 48%
See 2 more Smart Citations